Aspergillus Coinfection in a Hydatid Cyst Cavity of Lung in an Immunocompetent Host: A Case Report and Review of Literature - Aayush Adhikari; Surendra Khanal; Sagar Rana Magar; Srijana Thapa; Srijana Khati; Rajan Lamichhane; Kundan Marasini (Case Reports in Infectious Diseases)
Aspergilloma (a saprophytic infection) typically colonizes lung cavities due to underlying diseases such as tuberculosis, bronchiectasis, cavitary lung cancer, sarcoidosis, and pulmonary infarctions. Rarely, aspergilloma has been noted within a hydatid cyst. Even if this was the case, it is more common to find the coexistence of aspergilloma and pulmonary echinococcal cysts in immunocompromised individuals. It is, however, very uncommon to find this coinfection in normal immune status individuals. Here, we report on the successfully treated case of a 30-year-old immunocompetent female from Western Nepal with histologically proven coinfection by these two pathogens. She had a prolonged history of exposure to domesticated dogs. She suffered from hemoptysis from time to time for 3 years with increased frequency in the last 30 days. She was misdiagnosed clinically during a past medical visit at a local health center. Her computed tomography (CT) scans showed well-defined nonenhancing cystic lesions in the anterior basal segment of the right lower lobe adjacent to the major fissure. She underwent enucleation of the cyst via right posterolateral thoracotomy. On further histopathological evaluation, laminated membranes of the ectocyst along with fungal elements were found, and periodic acid-Schiff (PAS) staining revealed Aspergillus in the form of septate hyphae and acute angle branching. Owing to patient’s economic constraints and unavailability in our center, DNA testing and molecular characterization could not be performed which further highlights the essence of diagnosing and managing such cases in resource poor settings. Eventually, we reviewed 12 confirmed cases of this coinfection in immunocompetent individuals during a period of 7 years (2015–2022) comparing them to a systematic review of 22 confirmed cases of the same coinfection from 1995 to 2014.